DIVERSITY STUDY OF PREDACEOUS INSECT FAUNA IN MAJOR KHARIF CROP AGRO-ECOSYTEM IN AKOLA MAHARASHTRA (INDIA) - BHAUSAHEB NAIKWADI,; S. M. DADMAL,; SAMADHAN JAVALAGE, (The Bioscan, 2015)
The present paper deals with the diversity of predatory fauna for comparing the species richness and evenness in kharif crop agro-ecosystem of Akola district, Maharashtra.During course of investigations,abundant predatory insect fauna was recorded near Akola vicinity (42.28%) might be due to cultivation of diversified agro ecosystem. In terms of highest predatory fauna it was noticed that order Coleoptera contributing (-0.36628), followed by Hemiptera (-0.31415) these two order species showed abundance predatory fauna in this locality. However, moderate to rich species biodiversity of predatory fauna was noticed as per Shannon Biodiversity Index (H’=1.744) in Akola vicinity during kharif 2010-11. Simpson index value was 0.78. The Evenness index had a value of 0.80. Predatory species exhibited variation in their occurrence. Along with the sepredaceous insect fauna some non insect predatory fauna from Arachnida (-0.255), viz; spiders Neoscona spp, Oxyopes spp, Thomisus spp., Pseusetia spp. was found on various kharif crops.Out of the 4 species of spiders recorded Neoscona species was found to be predominant species which predating on all types of pests.The results of present study revealed the occurrence of 9 predatory orders and 14 families.In cotton agro-ecosystem highest (34.89%) predatory fauna was recorded followed by soybean (30.87%).